2014
DOI: 10.1172/jci72271
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of diabetic kidney disease

Abstract: Diabetic kidney disease (DKD) is the leading cause of kidney failure worldwide and the single strongest predictor of mortality in patients with diabetes. DKD is a prototypical disease of gene and environmental interactions. Tight glucose control significantly decreases DKD incidence, indicating that hyperglycemia-induced metabolic alterations, including changes in energy utilization and mitochondrial dysfunction, play critical roles in disease initiation. Blood pressure control, especially with medications tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
558
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 722 publications
(604 citation statements)
references
References 105 publications
7
558
0
4
Order By: Relevance
“…Inflammation plays an important role throughout the pathogenesis of diabetic microvascular complications [28,30,31]. Kowluru et al showed that high glucose significantly increased the activated caspase-3 and NF-κB levels, which remained Bar, mean ± SD; **p < 0.01 vs the respective negative control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation plays an important role throughout the pathogenesis of diabetic microvascular complications [28,30,31]. Kowluru et al showed that high glucose significantly increased the activated caspase-3 and NF-κB levels, which remained Bar, mean ± SD; **p < 0.01 vs the respective negative control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of this protective mechanism in miR-146a Diabetic nephropathy (DN) is the leading cause of CKD and ESRD. [1][2][3][4][5][6] Development and progression of DN involve a complex interplay among metabolic, hemodynamic, growth, and inflammatory factors. 1,3,[7][8][9][10][11][12][13] The progressive decline in renal function during DN is a result of a multitude of pathologic changes in the kidneys, including glomerular and tubular hypertrophy, macrophage infiltration, extracellular matrix (ECM) accumulation in multiple renal cells, mesangial expansion, endothelial dysfunction, and podocyte injury.…”
mentioning
confidence: 99%
“…Tubular dysfunction has been reported in the absence of microalbuminuria in patients with diabetes mellitus. Early tubular injury has been reported in patients with diabetes mellitus whose glomerular function is intact [7].…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxic milieu in early stage diabetic nephropathy is aggravated by manifestations of chronic hyperglycemia-abnormalities of red blood cells, oxidative stress, sympathetic denervation of the kidney due to autonomic neuropathy, and diabetes-mellitus-induced tubular apoptosis; as such, tubulointerstitial hypoxia in diabetes mellitus might be an important early event [7][8][9]. Analysis of the Vitamin D3 levels in relation to albuminuria levels in patients with diabetic nephropathy shows negative correlation (R=-0.59, р<0.001) ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%